Diversity Of Liana Plants Available In The Konak Protected Forest Area, Kepahiang District, Kepahiang Regency - Sulaiman, Endang; Nopriyeni, Nopriyeni; Darwin, Carles; Lusianti, Anggi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
This study aims to determine the diversity of lianas found in the Konak Protection Forest, Kepahiang District, Kepahiang Regency. Penelitian ini menggunakan metode purposive sampling yang dilaksanakan pada bulan Januari-Februari 2022. Pengambilan sampel menggunakan  metode plot, dimana petakan plot disusun sepanjang garis transek secara sistematik. This study used a purposive sampling method,which was carried out in January-February 2022. Sampling used the plot method, where plots were arranged systematically along transect lines. The samples obtained were then identified at the Bengkulu Muhammadiyah University Laboratory. The results of the study in the Konak Protection Forest, Kepahiang District, Kepahiang Regency, obtained 12 families which included 20 species, namely Araceae (Pothos scandens), Arecaceae (Calamus javensis, Korthalsia rigida), Asteraceae (Mikania micrantha), Basellaceae (Anredera cordifolia), Convolvulaceae (Merremia peltata).(Merremia vitifolia), Cucurbitaceae (Momordica charantia), Dioscoraceae (Dioscorea hispida, Dioscorea alata), Fabaceae (Calopogonium mucunoides, Centrosema pubescens, Psophocarpus tetragonolobus), Menispermoideae (Cycle barbata, Pericampylus galusia (Passiflora crispa), Passiflora Piperaceae (Piper nigrum, Piper retrofracrum), Schizaeaceae, (Lygodium flexuosum). Based on the species diversity index (H') of lianas in the Konak Protection Forest area, Kepahiang District, Kepahiang Regency, which is 1.211, and is included in the category of medium diversity. With temperatures ranging from 25°C-30°C, humidity between 55% - 89%, and light intensity ranging from 507 Lux – 2115 Lux.Keywords: diversity, liana, konak protected forest